MAKING MOROS : Imperial Historicism and American Military Rule in the Philippines' Muslim South - Hawkins, Michael, (Michael C.) (DeKalb, Illinois : Northern Illinois University Press, 2013)
"This book offers a unique look at the colonial creation of Muslim subjects during the early years of American rule in the southern Philippines. It examines the Islamic Philippines during its most formative period in modernity--a period indispensible to discussions of integration in the Filipino Islamic South"--
Imperial taxonomies -- Disruptions -- Capitalism as panacea -- Modernity, colonial guilt, and the price of transcendent progress -- Epilogue : the American military period in historical memory.
"Published by the Northern Illinois University Press in conjunction with the Center for Southeast Asian
Studies, DeKalb, Illinois"--Title page verso.
Includes bibliographical references (pages 173-181) and index.
Keywords: Imperialism -- History; Military occupation -- Social aspects -- Philippines -- Mindanao Island -- History; Military occupation -- Social aspects -- Philippines -- Sulu Archipelago -- History; Muslims -- Philippines -- Mindanao Island -- History; Muslims -- Philippines -- Sulu Archipelago -- History